2019
DOI: 10.1002/cphc.201900145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pressure and pH on the Physical Stability of an I‐Motif DNA Structure

Abstract: The thermodynamic stability of a cytosine(C)‐rich i‐motif tract of DNA, which features pH‐sensitive [C..H..C]+ moieties, has been studied as function of both pressure (0.1–200 MPa) and pH (3.7–6.2). Careful attention was paid to correcting citrate buffer pH for known variations that stem from changes in pressure. Once pH‐corrected, (i) at pH >4.6 the i‐motif becomes less stable as pressure is increased (KD decreases), giving a small negative volume change for dissociation (ΔDV°) of the i‐motif – a conclusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Because of the small value of the volume change, the stability of i -motifs is nearly insensitive to hydrostatic pressure. In agreement with this expectation, the transition temperatures of the heat-induced i -motif-to-coil transitions do not change or change very weakly with pressure [ 57 , 102 , 103 ]. When treating the volumetric properties of i -motif structures derived from measurements at high pressures, it is important to account for the pressure-induced changes in the pH of the solution, as the stability of an i -motif critically depends on pH.…”
Section: Differential Volume Of Four-stranded and Single-stranded Conformationsmentioning
confidence: 52%
See 1 more Smart Citation
“…Because of the small value of the volume change, the stability of i -motifs is nearly insensitive to hydrostatic pressure. In agreement with this expectation, the transition temperatures of the heat-induced i -motif-to-coil transitions do not change or change very weakly with pressure [ 57 , 102 , 103 ]. When treating the volumetric properties of i -motif structures derived from measurements at high pressures, it is important to account for the pressure-induced changes in the pH of the solution, as the stability of an i -motif critically depends on pH.…”
Section: Differential Volume Of Four-stranded and Single-stranded Conformationsmentioning
confidence: 52%
“…Table 5 lists changes in volume, Δ V , measured for heat-induced and pH-induced i -motif-to-coil transitions. In contrast to G-quadruplexes, which are characterized by large negative changes in volume upon unfolding, i -motif-to-single strand transitions exhibit near-zero changes in volume [ 57 , 102 , 103 ]. Because of the small value of the volume change, the stability of i -motifs is nearly insensitive to hydrostatic pressure.…”
Section: Differential Volume Of Four-stranded and Single-stranded Conformationsmentioning
confidence: 99%
“…Robustness and evolvability may also be modeled computationally using flow reactor simulations (58) . Forms of robustness other than mutational robustness, like the robustness of protein and RNA interaction networks, and robustness to environmental conditions such as temperature (59) , pressure and pH fluctuations (60) can also be explored. The study of the interplay between robustness and evolvability informs our understanding of how new functions evolve in proteins and RNAs (31,(61)(62)(63) , the proposed transition from an RNA world (64) and will help biomolecular engineering of functions under mutational and environmental challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Under favorable solution conditions, G-rich DNA strands fold into a four-stranded G-quadruplex conformation, while C-rich strands adopt a four-stranded i-motif conformation. There is increasing evidence that noncanonical tetraplex structures, including G-quadruplexes and i-motifs, do exist in the cell and perform important regulatory functions in various genomic events. ,, To unveil the balance of forces involved in interconversions between duplex and tetraplex structures, the thermal, thermodynamic, and kinetic properties of G-quadruplex and i-motif structures have been extensively studied. ,, These studies have revealed a complex web of interactions governing transitions between the conformational states available to G-rich and C-rich DNA molecules. ,, On the other hand, volumetric investigations of tetraplex nucleic acid structures are scarce; in fact, the volumetric description of such systems has just begun to emerge. The volumetric properties of biopolymers provide important insights into the roles of hydration and intramolecular fluctuations in their stability and recognition events which are complementary to insights derived from more conventional structural, calorimetric, and spectroscopic studies. ,, , …”
Section: Introductionmentioning
confidence: 99%